ANALISIS KONSEP KEPEMIMPINAN PENDIDIKAN IBNU QAYYIM AL-JAUZIYYA - Fatmariyanti, Yanti; Fauzi, Anis; Bachtiar, Machdum (AKSI: Jurnal Manajemen Pendidikan Islam, 2023)
Leadership as part of management has a strategic and dominant role and position in managing an organization. Ibn Qayyim al Jauziyyah in his work explains that the main object of Islamic education activities is human beings with all the elements that complement them, namely their spirit, mind and body, these three things should be given development according to their respective abilities. This study aims to find out about the leadership management model of Ibn Qayyim al Jauziyyah's Islamic Education and its relation to Islamic Education. This research uses library research methods (Library Research). Ibn Qayyim Al Jauziyyah's leadership model is based on the Qur'an and Sunnah which are relevant and can be adapted from time to time. In leadership model theory, it is in line with the transformational leadership model.